THE IMPLEMENTATION OF ZERO WASTE AND SUSTAINABILITY IN ROCKSALT BEACH CLUB BATAM - Viviana, Viviana; Tito Pratama; Wahyudi Ilham; Dailami, Dailami (Bajang Institute, 2024)
The ongoing industrial activities including tourism industry can cause ecosystem destruction damage. The primary objective of this study is to analyze how these practices are integrated into the bar's operations and to assess their effectiveness in managing waste and promoting sustainability. Zero waste is an initiative move that taken by individuals or groups in order to reduce the amount of waste produced every day. It has been estimated by the National Waste Management Information System that 40.9% of the waste produced comes from food waste. This research employs qualitative research methods, including comprehensive observations, direct interviews, and the integration of data obtained from a variety of reliable sources. Rocksalt Beach Club serves as an exemplary case study due to its commitment to environmental sustainability and innovative waste reduction techniques. The successful application of zero waste principles such as reduction, reuse, recycling, and composting within the bar's operations. By incorporating these practices, the restaurant not only minimizes waste but also fosters a culture of responsibility and care towards both local and global communities. This research aims to analyze the methods used in order to approach to waste management that can lead environment benefits to achieve zero waste and sustainability at Rocksalt Beach Club.